Spremembe rabe tal na območju občine Juršinci - Žiberna, Igor (Revija za geografijo, 2021)
In this article, we analyse land-use change in the municipality of Juršinci. In the first part of the article we discuss the changes in land use in relation to some natural-geographical characteristics in the period 2000-2021. We also discuss the most frequent directions of land use change. In the second part of the paper, we look at the changes in vineyard areas. In this context, we compared the extent of vineyard area in 1824 with the current situation. We also analyse the utilisation of quality vineyard areas in the past and today.
Keywords: abandonment of arable land; Franciscan cadastre; Franciscejski kataster; Juršinci; land use; obdelovalne površine; Ptujske gorice; raba tal; vinogradništvo; viticulture